У пошуках нового суб’єкта історії: проект «Усна історія деколективізації в Україні 1990-х рр. – селянський досвід» - Ханенко-Фрізен, Н. (Український історичний журнал, 2010)
У статті йдеться про усно-історичний проект, який, на думку автор-
ки, безпосередньо стосується процесу деоб’єктивізації соціальних аґентів
історії – процесу, що розпочався у східноєвропейських суспільствознавчих
студіях із розпадом попереднього політичного ладу. Зокрема, ідеться про
те, яким чином нещодавно реалізований проект «Усна історія деколективі-
зації в Україні 1990-х рр. – селянський досвід» при визначенні свого суб’єкта
дослідження виокремлює ще одного активного аґента української історії
XX ст. – розколгоспненого селянина. Oral historians find themselves in a unique position within the network of
various disciplines of social sciences and humanities, from where they successfully
challenge established principles of representation of the past, history, and
society. Addressing the question of a unique role of oral history in reconstructing
historical meta-narratives, the author turns to discuss one of the projects conducted
in Ukraine in 2007–2008, «Oral History of Decollectivization of Ukraine
in the 1990s». The goal of the project was to document people’s perspectives on
decollectivization and to register a particular collective stance which, as the
author expected, would emerge through multiplicity of the recorded testimonies.
The project encompassed ten oblasts where local interviewers recorded interviews
with former members of collective farms. The article evaluates the project’s
claims and methods in relationship to its attempt to locate, explore, understand
and perhaps redeem yet another subject of the Ukrainian history, «Ukrainian villager, decollectivized».